Quantum tunneling of hydrogen atom transfer affects mandrel degradation in inertial confinement fusion target fabrication - Yu Zhu; Xinrui Yang; Famin Yu; Rui Wang; Qiang Chen; Zhanwen Zhang; Zhigang Wang (iScience, 2022)
Summary: Poly-α-methylstyrene (PAMS) is considered as the preferred mandrel material, whose degradation is crucial for the fabrication of high-quality inertial confinement fusion (ICF) targets. Herein, we reveal that hydrogen atom transfer (HAT) during PAMS degradation, which is usually attributed to the thermal effect, unexpectedly exhibits a strong high-temperature tunneling effect. Specifically, although the energy barrier of the HAT reaction is only 10−2 magnitude different from depolymerization, the tunneling probability of the former can be 14–32 orders of magnitude greater than that of the latter. Furthermore, chain scission following HAT will lead to a variety of products other than monomers. Our work highlights that quantum tunneling may be an important source of uncertainty in PAMS degradation, which will provide a direction for the further development of key technology of target fabricating in ICF research and even the solution of plastic pollution.